2019
DOI: 10.9734/bji/2019/v23i230074
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of Lactic Acid Bacteria with D-tagatose Production Capability

Abstract: Aims: D-tagatose is a natural ketohexose which can be used as a functional sweetener in foods, diary and beverages products. Isolation of new bacterial strains having the ability to produce Dtagatose is a continuously trending topic of research. Study Design: Screening of strains with D-tagatose production by identification and determination of its ability to produce D-tagatose content. Place and Duration of Study: School of Food and Biological Engineering, Jiangsu University between May 2018 and April 2019. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…This result indicates that the bacterial isolates possess the ability to produce D-tagatose. Similar study performed with lactic acid bacteria showed a much lower D-tagatose yield with 3.134 g/L for Lactobacillus salivarius [22].…”
Section: Qualitative and Quantitative Analysis Of D-tagatosesupporting
confidence: 69%
“…This result indicates that the bacterial isolates possess the ability to produce D-tagatose. Similar study performed with lactic acid bacteria showed a much lower D-tagatose yield with 3.134 g/L for Lactobacillus salivarius [22].…”
Section: Qualitative and Quantitative Analysis Of D-tagatosesupporting
confidence: 69%